The Antarctic Treaty System: Resource Development, Environmental Protection or Disintegration? - Rothwell, Donald R. (ARCTIC, 1990)
The Antarctic Treaty System has successfully managed Antarctica and the surrounding Southern Ocean since 1961 despite the existence of conflicting sovereignty claims and calls from the Third World for greater international participation in the continent's management. The spectre of unregulated mining activities in Antarctica caused the parties to the Antarctic Treaty to negotiate the Convention for the Regulation of Antarctic Mineral Resource Activities in 1988. However, the entry into force of the convention is now being challenged by Australia and France, who propose a prohibition on mining in Antarctica and favour the negotiation of a comprehensive environmental protection regime for the Antarctic. The development of a world park in Antarctica has been promoted since 1972, and during the 1980s various international environmental organizations gave enthusiastic support to the concept. A meeting of the Antarctic Treaty Consultative Parties in 1989 resolved to further discuss in 1990 the implementation of comprehensive environmental protection measures in Antarctica. While 1990 may be a pivotal year in the current debate over the environmental future of Antarctica, 1991 is potentially more significant, as the Antarctic Treaty will then become eligible for a comprehensive review. This raises the prospect of substantial changes to the Antarctic regime.